2017
DOI: 10.1021/acs.inorgchem.7b00658
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Photophysical Properties of Photostable Benzo[b]phospholeP-Oxide-Based Fluorophores

Abstract: We previously reported that constrained 2-phenylbenzo[b]phosphole P-oxides bearing a diphenylamino group show high photostability and thus are promising dyes for fluorescence imaging. Herein we investigated the impact of the bridging moieties on their photophysical properties. A series of benzo[b]phosphole P-oxides constrained with various carbon or silicon bridges were synthesized. All of these compounds showed significant solvatochromism in fluorescence due to the intramolecular charge-transfer character in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The components of S TDM also suggest that CBF-S has lower anisotropy in its shape (low λ S and S LX~0 .23), which is the main reason for the low S TDM , similarly to the cases found on CP2 and CBM. Originally, the phenyl group attached to the phosphorus has been designed and required because of the synthetic reason, ie, availability of the starting materials and the stability toward the reaction conditions 39,47,48 . Here it is theoretically suggested that the structural nature, ie, >P(=O)Ph, also plays an important role in realising negative fluorescence anisotropy of phosphole oxide-based dyes in the present NLCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The components of S TDM also suggest that CBF-S has lower anisotropy in its shape (low λ S and S LX~0 .23), which is the main reason for the low S TDM , similarly to the cases found on CP2 and CBM. Originally, the phenyl group attached to the phosphorus has been designed and required because of the synthetic reason, ie, availability of the starting materials and the stability toward the reaction conditions 39,47,48 . Here it is theoretically suggested that the structural nature, ie, >P(=O)Ph, also plays an important role in realising negative fluorescence anisotropy of phosphole oxide-based dyes in the present NLCs.…”
Section: Resultsmentioning
confidence: 99%
“…Five phosphole oxide-based fluorescent dyes (racemic mixtures)-(CP2), (CBM), (CBX), (CBF) and (CNX) (Fig. 2b)-were synthesised according to previously reported methods 39,[46][47][48] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the ICT related research was performed with variations among the donor, the acceptor, and the bridging units. To enhance the stimuli‐responsiveness and to broaden the functionality of ICT related fluorescent systems, proton transfer, cyclization, and other intramolecular interactions have been employed to regulate the degree of conjugation of the structure between the donor and the acceptor. One possibility for the design is to introduce an alkynyl group into the bridge connecting the donor and the acceptor as a part of the conjugated structure.…”
Section: Introductionmentioning
confidence: 99%
“…30 However, a detailed rationalization of the high photostability should require further experimental investigations especially into the excited state dynamics, which is currently in progress in our laboratory. Interestingly, we have also demonstrated that a silicon bridged congener shows comparable photostability.…”
mentioning
confidence: 99%